Aging and hypertension in kidney function decline: A 10 year population-based study - Jaques, David A.; Vollenweider, Peter; Bochud, Murielle; Ponte, Belen (Frontiers in Cardiovascular Medicine, 2022)
Background: Aging is associated with a physiological decline in kidney function (KFD). In this study, we aimed to describe the impact of age on the rate of KFD and its interplay with risk factors for chronic kidney disease (CKD), considering mainly hypertension (HT), in the general population. Methods: Participants of European descent, aged 35 to 75, were recruited from a populational cohort in Lausanne, Switzerland. Participants with a 10-year follow-up were selected. KFD was defined as the difference in estimated glomerular filtration rate (eGFR) between baseline and follow-up, divided by the observation period. Multivariate linear regressions were used with KFD as the outcome and age as the main predictor. HT was tested as a modifying factor. Results: We included 4'163 participants with mean age 52.2 +/- 10.4, 44.7% men, 31.9% HT and 5.0% diabetics. Mean baseline eGFR was 85.9 +/- 14.6 mL/min/1.73m2. Mean KFD was -0.49 +/- 1.08 mL/min/1.73m2 per year with 70% of participants decreasing their eGFR during follow-up. The relationship between age and KFD was non-linear and age was divided in tertiles. Old participants had faster rates of KFD as compared to young and middle-age participants (p<0.001). A significant interaction was found between age and HT on KFD prediction (p<0.001). In HT participants, KFD was significantly different across tertiles of age (p<0.001). On contrary, KFD was not different across tertiles of age in non-HT participants. Conclusion: A physiological KFD is present over time in the general population. Age contributes non-linearly to the rate of this decline with older subjects declining the fastest. The presence of HT is a major contributing factor in this setting as KFD worsened with age only in hypertensive participants. Thus, HT represents an important pathological factor aggravating the age-related physiological decline in eGFR in the general population.